Knowing Beans: Human Mirror Mechanisms Revealed Through Motor Adaptation - Glenberg, Arthur M.; Lopez-Mobilia, Gabriel; McBeath, Michael; Toma, Michael; Sato, Marc; Cattaneo, Luigi (Frontiers in Human Neuroscience, 2010)
Human mirror mechanisms (MMs) respond during both performed and observed action and appear to underlie action goal recognition. We introduce a behavioral procedure for discovering and clarifying functional MM properties: Blindfolded participants repeatedly move beans either toward or away from themselves to induce motor adaptation. Then, the bias for perceiving direction of ambiguous visual movement in depth is measured. Bias is affected by a) number of beans moved, b) movement direction, and c) similarity of the visual stimulus to the hand used to move beans. This cross-modal adaptation pattern supports both the validity of human MMs and functionality of our testing instrument. We also discuss related work that extends the motor adaptation paradigm to investigate contributions of MMs to speech perception and language comprehension.